2018
DOI: 10.4102/apsdpr.v6i1.217
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of prevalence of unethical tendering practices at national and subnational levels in Nigeria

Abstract: Nigeria has recently renewed efforts towards stamping out corruption in every area of its national life. Given that construction procurement is particularly prone to corrupt practices, this study investigated the prevalence of unethical tendering practices in the Nigerian public sector. In particular, a comparison to bare the similarities or differences in the prevalence of unethical tendering practices at national and subnational levels is scarcely available in literature. This study’s objective was to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
24
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(36 citation statements)
references
References 33 publications
7
24
2
Order By: Relevance
“…Literature reports on the presence of ethical misconducts across the various phases and stages of construction contracts or projects (Mukumbawa and Muya, 2013; Sohail and Cavill, 2006). However, other studies have categorically stated that the presence of ethical misconducts is very prevalent during the tendering stage of construction contacts as compared to all other stages (Ogbu and Asuquo, 2018; Ameyaw et al , 2017; Shan et al , 2016; Wells, 2013; Adnan et al , 2012; Azher et al , 2011; Abdul-Rahman et al , 2010; Bowen et al , 2007; Shakantu, 2006; Vee and Skitmore, 2003). Ogbu and Asuquo (2018) revealed that in Nigeria, the three most prevalent unethical tendering practices are contractor-based and include: the offering of bribes by competitors to gain access to confidential tendering information; overstating of capacity, experience and qualifications by competitors to secure construction contracts and using different firms to tender for the same project by the same owner(s).…”
Section: Literature Reviewmentioning
confidence: 96%
See 4 more Smart Citations
“…Literature reports on the presence of ethical misconducts across the various phases and stages of construction contracts or projects (Mukumbawa and Muya, 2013; Sohail and Cavill, 2006). However, other studies have categorically stated that the presence of ethical misconducts is very prevalent during the tendering stage of construction contacts as compared to all other stages (Ogbu and Asuquo, 2018; Ameyaw et al , 2017; Shan et al , 2016; Wells, 2013; Adnan et al , 2012; Azher et al , 2011; Abdul-Rahman et al , 2010; Bowen et al , 2007; Shakantu, 2006; Vee and Skitmore, 2003). Ogbu and Asuquo (2018) revealed that in Nigeria, the three most prevalent unethical tendering practices are contractor-based and include: the offering of bribes by competitors to gain access to confidential tendering information; overstating of capacity, experience and qualifications by competitors to secure construction contracts and using different firms to tender for the same project by the same owner(s).…”
Section: Literature Reviewmentioning
confidence: 96%
“…According to Harris and McCaffer (2013), negotiation is only a means of communication between the client and the contractor and the exchange of data and documents to conclude clients’ decisions. Despite the numerous advantages associated with tendering (Morote and Vila, 2012; Huang, 2011; Plebankiewiez, 2009; Ogunsemi and Aje, 2006; Olatunji, 2006; Nwachukwu, 2006), it is still plagued with series of unethical practices (Ogbu and Asuquo, 2018; Shan et al , 2016; Wells, 2013; Adnan et al , 2012; Azher et al , 2011; Abdul-Rahman et al , 2010; Bowen et al , 2007; Shakantu, 2006; Vee and Skitmore, 2003).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations